Zur Frage der Zeilenendpausen im Genfer Psalter - Aeschbacher, Gerhard (Jahrbuch für Liturgik und Hymnologie, 1985)
It is by the revisions of our hymn book that the unsettled difficulty of the line-end rest in the psalter of Geneva has become a topic again. The author does not agree with the prevailing opinion: To his thinking those rests are meant for structure and breath-taking. This is clearly shown by the history of notation of the evangelical community singing. In the time of the reformation one and the same hymn was sometimes noted with line-end bar, sometimes with a rest sign, or eventually with a fermata, or even without any line-end sign. In the Swiss hymn books of the 17th century the psalter and the hymns from the Lutheran area are generally noted with rest signs. This was probably due to the influence of the Genevan settings. The line-end bar prevails towards the end of the 17th and in the 18th century. The original functions of the line-end rest and (not much later) of the bar are not understood any more. The very few historical hints are setting the same trend: In Heinrich Schütz's preamble to the Becker psalter, in the 12th chapter of "Droict chemin de Musique" by Loys Bourgeois, and in the "Erklärung der Noten" in Bernese hymn books. Schütz and Bourgeois clearly distinguish psalm singing from mensural music. The author's thesis is also confirmed, if we are aware of the prosodic character of the Genevan psalter, which in a free way adapts its rhythmic structure to the flow and stanza of French verses. Modern notation should be unequivocal, unmistakeable. It should correspond to the character of the tune and be a help for practice.